Womens Representation in Cosmopolitan Magazine - Kahanna, Mutia; Endrizal (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research is aimed at looking at the portrayal of women in the media, especially in Cosmopolitan magazines. Cosmopolitan magazine advertisements use sex appeal in packaging their messages. Sex appeal is built through female sexuality and sensuality. This is reflected in the verbal and visual aspects of advertising. Verbal aspects can be seen from the text in the headline, body copy, and closing. Visual aspects can be observed vectorially, modality, and composition. The analysis was carried out using Roland Barthes' semiotic approach at the level of denotation and connotation. In collecting data, the research tries to see examples of advertisements in cosmopolitan magazines which are categorized into sensual, romantic, and erotic sections. In collecting data, this study used qualitative methods. This research type is a library (library study) using a semiotic approach. The research data were collected from relevant literature, journals, and previous studies.